Bone marrow‐derived stromal cells are more beneficial cell sources for tooth regeneration compared with adipose‐derived stromal cells. (18th June 2015) - Ye, Lanfeng; Chen, Lin; Feng, Fan; Cui, Junhui; Li, Kaide; Li, Zhiyong; Liu, Lei
Abstract: Tooth loss is presently a global epidemic and tooth regeneration is thought to be a feasible and ideal treatment approach. Choice of cell source is a primary concern in tooth regeneration. In this study, the odontogenic differentiation potential of two non‐dental‐derived stem cells, adipose‐derived stromal cells (ADSCs) and bone marrow‐derived stromal cells (BMSCs), were evaluated both in vitro and in vivo. ADSCs and BMSCs were induced in vitro in the presence of tooth germ cell‐conditioned medium (TGC‐CM) prior to implantation into the omentum majus of rats, in combination with inactivated dentin matrix (IDM). Real‐time quantitative polymerase chain reaction (RT‐qPCR) was used to detect the mRNA expression levels of odontogenic‐related genes. Immunofluorescence and immunohistochemical assays were used to detect the protein levels of odontogenic‐specific genes, such as DSP and DMP‐1 both in vitro and in vivo. The results suggest that both ADSCs and BMSCs have odontogenic differentiation potential. However, the odontogenic potential of BMSCs was greater compared with ADSCs, showing that BMSCs are a more appropriate cell source for tooth regeneration.